2016
DOI: 10.4238/gmr.15017541
|View full text |Cite
|
Sign up to set email alerts
|

Association of the interleukin-10 gene -1082A/G genetic polymorphism with risk of ischemic stroke in a Chinese population

Abstract: ABSTRACT.We investigated the possible association between two single nucleotide polymorphisms of IL10 (-1082A/G and -592C/A) and susceptibility to ischemic stroke. In total, 335 patients with proven ischemic stroke and 335 control subjects were recruited from Xinxiang Central Hospital between March 2013 and May 2015. The IL10 -1082A/G and -529C/A polymorphisms were investigated by polymerase chain reaction-restriction fragment length polymorphism. When compared with the control subjects, patients with ischemic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
6
0
3

Year Published

2017
2017
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 23 publications
0
6
0
3
Order By: Relevance
“…The relation of lower IL-10 levels with the development of vascular complications has been proposed in some studies. For example, during the stroke, IL-10 levels are below normal [21]. In preeclamptic women, the reduction in Figure 4 The endogenous absence of IL-10 associated with Ang II positively modulates vascular expression of total and phosphorylated ERK 1/2.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The relation of lower IL-10 levels with the development of vascular complications has been proposed in some studies. For example, during the stroke, IL-10 levels are below normal [21]. In preeclamptic women, the reduction in Figure 4 The endogenous absence of IL-10 associated with Ang II positively modulates vascular expression of total and phosphorylated ERK 1/2.…”
Section: Discussionmentioning
confidence: 99%
“…The relation of lower IL‐10 levels with the development of vascular complications has been proposed in some studies. For example, during the stroke, IL‐10 levels are below normal . In preeclamptic women, the reduction in IL‐10 receptors, as well as lower IL‐10 circulating levels, is observed, suggesting IL‐10 as a biomarker of preeclampsia .…”
Section: Discussionmentioning
confidence: 99%
“…IL1B took part in 5 pathways, and IL6 took part in 4 pathways which are NOD-like receptor signalling pathways, cytokine-cytokine receptor interactions, TNF-signalling pathway, and Rheumatoid arthritis pathways; CXCL1, CXCL2, and CXCL3 took part in 2-3 pathways including the TNF-signalling pathway, cytokine-cytokine Sex specific signaling analysis of ischemic stroke receptor interactions, and NOD-like receptor signalling pathways. Several studies have shown that immune responses including IL6 [34], IgA [35], CXCL16 [36], TNFSF4 [37], and IL10 [38] were involved in stroke. IL6 and infarction size were reported as independent predictors of short-term stroke outcome in young Egyptian adults [34].…”
Section: Discussionmentioning
confidence: 99%
“…Кроме того, много данных накоплено в отношении ассоциации полиморфизма гена IL-10 с атеросклерозом различных локализаций. Ассоциация носительства аллеля А полиморфного маркера A(-1082)G с развитием инсульта неоднократно выявлена в различных азиатских популяциях [15][16][17]. В исследовании PROSPER (Pravastatin in the Elderly at Risk) показана ассоциация риска развития инсульта с носительством генотипа -2849AA полиморфного маркера G (-2849) A гена IL-10 [18].…”
Section: Discussionunclassified
“…Целью исследования был анализ возможной ассоциации клинических и генетических факторов с развитием инсульта у больных, перенесших обострение ИБС. (7): [14][15][16][17][18][19][20][21][22].…”
unclassified